Over than three-year follow-up results of thermal ablation for papillary thyroid carcinoma: A systematic review and meta-analysis - Xue, JiaNan; Teng, DengKe; Wang, Hui (Frontiers in Endocrinology, 2022)
Background This study is a meta-analysis based on evidence-based medicine to explore the long-term (≥3 years) efficacy of thermal ablation in the treatment of papillary thyroid carcinoma (PTC). Methods We searched the PubMed, Embase, and Cochrane Library databases for studies published during the time between the establishment of the databases through June 2022. We included 13 non-randomized-controlled trials (non-RCTs) that reported the application of ultrasound-guided thermal ablation in PTC. We excluded studies that were repeated publications, research without full text, contained incomplete information, lacked data extraction, involved animal experiments, reviews, and systematic reviews. STATA 15.1 software was used to analyze the data. Results Tumor volume after thermal ablation at 3-year follow-up was significantly lower than pre-ablation (standardized mean difference [SMD] = -1.06, 95% CI: -1.32 -0.80). The pooled results indicated that the maximum diameter after thermal ablation at 3-year follow-up was significantly lower than pre-ablation (SMD = -1.93, 95% CI: -12.13 -1.73). The pooled results indicated that volume reduction rate (VRR) after thermal ablation at 3-year follow-up was 98.91% (95% CI: 97.98–99.83%), and complete disappearance rate (CDR) after thermal ablation at 3-year follow-up was 83% (95% CI: 67–94%). In addition, the incidence of newly discovered mPTC and lymph node metastases after thermal ablation was 0.3% (95% CI: 0.0–1.0%) and 0.0% (95% CI: 0.0–0.0%), respectively. Conclusion Overall, the long-term (≥3 years) efficacy of ultrasound-guided thermal ablation in the treatment of PTC was significant, with favorable disease progression. Ultrasound-guided thermal ablation can be considered an alternative approach for patients with PTC who refuse surgery or are unable to undergo surgery.